Emergent complexity in the decision-making process of chess players - Chacoma, Andrés Alberto (2025)
In this article, we study the decision-making process of chess players by using a chess engine to evaluate the moves across different pools of games. We quantified the decisiveness of each move during the games using a metric derived from the engine’s evaluation of the positions. We then performed a comparative analysis across players of varying competitive levels. Firstly, we observed that players face a wide spectrum of the decisiveness metric, evidencing the complexity of the process. By examining groups of winning and losing players, we found evidence where a decrease in complexity may be associated with a drop in players’ performance levels. Secondly, we observed that players’ accuracy increases in positions with high values of the decisiveness metric regardless of competitive level. Complementing this information with a null model where players make completely random legal moves allowed us to characterize the decision-making process under the simple strategy of making moves that minimize the decisiveness metric. Finally, based on this idea, we proposed a simple model that approximately replicates the global emergent properties of the system.